Hempel’s Dilemma and Research Programmes: Why Adding Stances is not a Boon - Prelević, Duško (Organon F, 2017)
Hempel’s Dilemma is intended to force physicalists to make an unfavourable choice between the current physics and a future physical theory. The problem with the first horn of the dilemma is related to the fact that current physics is, strictly speaking, inconsistent, while the problem with its second horn is that we do not know how a future, completed physical theory will look like. In this paper, the two strategies of avoiding the dilemma are compared and assessed: the attitudinal approach, according to which physicalism is a stance or an attitude, and Lakatosian approach, according to which physicalism is best understood as a research programme. It is argued that the latter approach ought to be preferred over the former approach because, among other things, it better explains how some physicalists and their opponents sometimes switch the sides, as well as why different physicalists undertake different activities within a given time interval.
Keywords: attitudinal approach; Hempel’s Dilemma; paradigm; physicalism; research programme; stance